ANALISIS PENGARUH PRAKTEK TATA KELOLA PERUSAHAAN (CORPORATE GOVERNANCE) TERHADAP KESULITAN KEUANGAN PERUSAHAAN (FINANCIAL DISTRESS): SUATU KAJIAN EMPIRIS - EMRINALDI NUR DP (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2007)
In general, this research had three objectives. The first objective was to examine the relationship between corporate governance on financial distress. The second objective was to examine the most influence variables of corporate governance on financial distress. Third objective was to confirm the past research. The study carried out 43 companies in Jakarta Stock Exchange, based frequencies during 2000-2002 periods. The analysis was started with descriptive statistic and paired sample t-test, to describe difference financial distress company and non financial distress company. Then, logit regression, or logistic regression or binary regression or pooled cross sectional logit regression used in examine the relationship and causality between corporate governance variables on financial distress. Two log likelihood, Cox and Snell R Square, and Hosmer and Lemeshow test, used to examine goodness on fit model. The result of first test described that variables of financial distress company and non financial distress company have deference on it’s average. But results of paired sample t-test didn’t have significant deference. Two log likelihood test, Cox and Snell R Square test, and Hosmes Lemeshow test denoted that the model which used in this research have goodness of fit. Pooled Cross Sectional Logit Regression presented that MGRO, INSTO, and BOARD have negative relationship on financial distress: While KI and AUDIT have positive relationship on financial distress. The result of logit regression indicates that AUDIT as the only one variable not supported by theory, while the others got support by theory. The most powerful effect on financial distress was belong KI, followed INSTO, MGRO, and BOARD.